AN ANALYSIS OF IDIOMS AND THEIR PROBLEMS FOUND IN THE NOVEL THE ADVENTURES OF TOM SAWYER BY MARK TWAIN (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2015)
Idiom is one of part language used in spoken language, written text and mass media. The purpose of this research is to find out idioms, their types, dominant type, and problems in understanding idioms. The object of the study was the English idiom in the novel The Adventure of Tom Sawyer. The data were the phrases or words or collocations found in the novel. The data were taken by reading, identifying, and inventorizing. Then, the data were analyzed by using the theories offered by Makkai related to the topic and find out the problems in that analysis. The result of this study, there were 796 idioms found in the novel and classified into 6 types of idiom offered by Makkai used. The dominant type of idiom used in the novel is phrasal verb idiom with 446 idioms (56.03%). In understanding the meaning of idiom, there are 4 problems existed, that are distinction between phrasal verbs that is idiom or not idiom; translation of idiom; understanding the closest meaning of idiom; and no grammatical rule of forming idiom. Therefore, readers should comprehend the idiomatic expressions used in novel to understand the meaning of idioms and the whole context of novel.